A argumentação externa da decisão judicial : uma análise do impacto da nova LINDB na hermenêutica constitucional - Paixão, Adenilton de Souza (2022)
The new LINDB presents new demands in decision-making arguments in Brazilian law. Interpretation would now have a strategic dimension, thinking about the consequences. But it maintains the need for another dimension, namely: argumentative explanation. We affirm that the changes promoted by the new LINDB, by demanding an increase in the quality of the decision-making arguments, had a positive impact on Brazilian law. To demonstrate this hypothesis, we chose the deductive method. The text presents some of the problems involving the interpretation process by presenting two models of decision-making justification: Proportionality and Regulatory Impact Analysis (RIA), in order to expose disagreements and approximations. The concern with the consequences, in the use of practical arguments, by both models of justification denotes its ability to operationalize art.20 of LINDB. Thus, it was followed with an intention to build a conciliatory proposal between theoretical models of interpretation and application of law: Primus, in order to clarify the dimension of explicit application of principles: An exhibition of texts from Alexy’s work, the Theory of Fundamental Rights, together with a presentation of criticism that the theory of principles suffered, in view of its method of applying principles as a model of normative theory for the judicial decision. Secundus presents legal certainty as a fundamental right and the role of efficiency in the promotion of justice. In this direction, the changes in LINDB require legal certainty and efficiency as a means of achieving the realisation of the law. The search for an explanation occupied with empirical data of the argumentation, in the field of the decision maker, that exploits its results and consequences, shows that AIR’s justification model has much to offer as an instrument of the decision-maker compromised with efficiency and legal certainty. Finally, it is proposed that a relationship of complementarity, in a methodological way, between the models of justification, is not only possible, as the new LINDB requires: it sets out a relationship of complementarity between proportionality and RIA, drawing on Cass R. Sunstein’s thesis on "not completely theorized agreements". Therefore, by suspending moral dilemmas in order to promote a practical and common result, it is possible to synthesize seemingly antagonistic rationalities. An example of this is the relationship of complementarity between proportionality and regulatory impact analysis (RIA). The teleological model of principles, as expounded by Alexy’s theory of principles, approaches the prognostic way of formulating practical judgments committed to the future, as expressed by AIR. Thus, the art. 20 of LINDB seems to imply a conflict of rationalities, but its proposal is another: the increase of the argumentative burden is patent with the regulation of the new legal text from decree 9830/19. The Regulatory Decree presents mechanisms such as public consultation, in order to increase both the information, through practical arguments, solving technical deficiencies of the decision-maker, and the legitimacy of the decision-making process. These recommendations enter the field of decision-making justification and can contribute to an increase in the quality of the decision-making argumentative burden: Articles 2, §2º, §3º, art.3º, art.18 and art. 19 of Decree-Law 9830/19 promote a communicational openness, a practical argument external to the Law, but never anti-legal. Therefore, we have an increase in intersubjective control by using practical arguments, giving coherence and predictability consistent with the type of objectivity appropriate to the legal system. Perhaps this will provide much-awaited legal certainty.